Facilitated enumeration of the silicate bacterium Paenibacillus mucilaginosus comb. nov. (formerly Bacillus mucilaginosus) via tetrazolium chloride incorporation into a double agar-based solid growth medium - Vardanian, Annie; Kurzbaum, Eyal; Farber, Yair; Butnariu, Monica; Armon, Robert (Folia microbiologica, 2018)
Accurate enumeration of Paenibacillus mucilaginosus (formerly Bacillus mucilaginosus) bacterium from environmental samples on solid medium is challenging owing to its extensive extracellular polysaccharides (EPS) excretion. In the present study, P. mucilaginosus enumeration has been facilitated by a simple modification: addition of triphenyl tetrazolium chloride (TTC) to growth medium and application of a second soft agar layer. Results show distinctively better and accurate colonies' count. This method can be applied to all bacterial species that produce excessive EPS that may interfere with direct count.
Keywords: polysacharidy; Paenibacillus; Coloring Agents; počet mikrobiálních kolonií; kultivační média; Tetrazolium Salts; tetrazoliové soli; Polysaccharides; Agar; barvicí látky; Culture Media; Colony Count, Microbial; agar